MATLAB Programming to Implement Quantum Walk Algorithm for Presenting Probability Distributions of Quantum Walks - Yuwana, Lila; Purwanto, Agus; Endarko, Endarko (Journal of Informatics and Mathematical Sciences, 2018)
There are numerous ideas that have been provided by quantum walks for new quantum algorithms. In this article, we surveyed the discrete quantum walk algorithm to present probability distributions. Moreover, we transformed the algorithm into MATLAB programming. Finally, the programming can be utilised to compare coin flip transformations that generate probability distributions as proposed in several previous articles and also to identify a unitarity of a coin flip transformation.